Predicting vasospasm after aneurismal subarachnoid hemorrhage with C reactive protein levels - Romero, Flávio Ramalho [UNESP]; Ducati, Luis Gustavo [UNESP]; Zanini, Marco Antônio [UNESP]; Cataneo, Daniele Cristina [UNESP]; Cataneo, Antônio José Maria [UNESP]; Gabarra, Roberto Colichio [UNESP] (Scientific Research Publishing, 2013)
Aim: The interest of inflammatory marker increased in the last years, even in preventing clinical outcome after subarachnoid hemorrhage (SAH). Our objective was to study the relationships between C-reactive protein levels and clinical outcome and the development of cerebral vasospasm after aneurismal SAH. Methods: One hundred adult patients with aneurismal SAH were prospectively evaluated. Glasgow Coma Scale (GCS) score, Hunt and Hess grade, Fisher grade, CT scans, digital subtraction angiography studies, transcranial doppler (TCD) and daily neurological examinations were recorded. Serial serum CRP measurements were obtained on daily between admission and 10th days. Glasgow Outcome Scale (GOS) and the modified Rankin Scale (mRS) were used to predict outcome. Results: A progressive increase in the CRP levels from the admission to the 3rd postictal day was observed, followed by a slow decrease until the 9th day. Hemodynamic changes in TCD were associated with higher serum CRP levels. Patients with lower GCS scores presented with increased CRP levels. Patients with higher Hunt and Hess grades on admission developed significantly higher CRP serum levels. Patients with higher admission Fisher grades showed increased levels of CRP. A statistically significant inverse correlation was established in our series between CRP serum levels and GOS and mRS scores on discharge and CRP levels. Conclusion: Increased CRP levels were strongly associated with poor clinical outcome. CRP levels can predict cerebral vasospasm and delayed ischemic deficits with higher statistic significance. There are relationships between hemodynamic chances in TCD and higher CRP levels.
Keywords: Intracranial vasospasm; Subarachnoid hemorrhage; C protein; Intracranial aneurism